Mothers of 0–3‐year‐old children with Down syndrome: Effects on quality of life. Issue 9 (30th September 2019) - Senses Dinc, Gulser; Cop, Esra; Tos, Tulay; Sari, Eyup; Senel, Saliha
Abstract: Background: The aim of this study was to assess the quality of life (QoL) of mothers of children with Down syndrome (DS) and the factors related to it. Methods: Seventy‐five DS child–mother diads and 54 healthy child–mother diads were included in this study. The brief World Health Organization Quality of Life scale – Turkish version (WHOQOL‐BREF‐TR), Symptom Check List‐90‐Revised (SCL‐90‐TR), Beck Depression Inventory, Beck Anxiety Inventory and Maslach Burnout Inventory (MBI) were completed by mothers to assess maternal QoL, burnout, anxiety, depression and general psychiatric symptoms. Results: Mothers of DS children had significantly higher SCL‐90 general symptom index scores, Beck depressive symptom scores and higher scores in all domains of the brief World Health Organization Quality of Life scale – (WHOQOL‐BREF‐TR) except the WHOQOL‐BREF‐TR‐psychological health domain. MBI personal achievement scores were weakly correlated with psychological health in mothers of DS children. There was a reverse correlation between comorbid disorders and the WHOQOL‐BREF‐TR psychological health domain, and a weak correlation between sex (having a baby girl with DS) and increased WHOQOL‐BREF‐TR physical health domain score. Number of offspring was negatively correlated with maternal social quality of life. Conclusion: Mothers of children with DS are negatively affected in terms of QoL and mental health, even in the early period. It would be useful to systematically screen these mothers and to refer them for appropriate intervention at an early stage.